The Role of Content Creators on Cryptocurrency Investment Decisions in Gen-Z Mediated by Digital Financial Literacy - Trevina, Valisha; Kohardinata, Cliff (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to analyze the influence of content creators on cryptocurrency investment decisions in generation Z, with digital financial literacy as a mediating variable. The research used quantitative methods by distributing questionnaires and obtaining 111 research samples from gen-Z who are active on social media and have experience in cryptocurrency investment. The data was processed through path analysis test and sobel test. Based on the results of the study found that the role of content has a direct correlation with investment decisions, the role of content has a significant positive effect on digital financial literacy, digital financial literacy has a significant positive effect on crypto investment decisions, and the mediating variable of digital financial literacy can mediate the effect of the role of content creators on cryptocurrency investment decisions.Keyword: Role of Content Creator; Digital Financial Literacy; and Cryptocurrency Investment